Obsessive-Compulsive Spectrum Symptoms Are Associated With Functional Impairment in Children and Adolescents With Psychosis Risk Syndrome: The CAPRIS Study - Vergara, Laura; de la Serna, Elena; Sugranyes, Gisela; Puig, Olga; Ilzarbe, Daniel; Fortea, Adriana; Tor, Jordina; Muñoz-Samons, Daniel; Rodriguez-Pascual, Marta; Alvarez-Subiela, Javier; Dolz, Montserrat; Baeza, Inmaculada (The journal of clinical psychiatry, 2023)
To compare clinical and functional variables among 3 groups of children and adolescents: subjects at clinical high risk for psychosis (CHR-P) who also have obsessive-compulsive symptoms (OCS), CHR-P patients without OCS, and healthy controls (HC). A total of 128 CHR-P patients and 98 HC between the ages of 10 and 17 years were recruited as part of a multicenter prospective longitudinal study conducted in Spain between January 1, 2011, and December 31, 2018, with diagnoses made for CHR-P using the Scale of Prodromal Symptoms (SOPS). Two groups were obtained based on Leyton Obsessional Inventory-Child Version (LOI-CV) scores: 64 CHR-P patients with OCS (OCS+) and 64 CHR-P patients without OCS (OCS-). Clinical variables were analyzed with a generalized linear model. Overall, 128 CHR-P patients, 64 (50%) with OCS (mean ± SD age = 15.5 ± 1.4 years, 34.4% male), 64 CHR-P patients without OCS (mean ± SD age = 15.1 ± 1.9 years, 34.4% male), and 98 HC (mean ± SD age = 15.5 ± 1.5 years, 42.9% male), of whom 19 (19.5%) had OCS, were included. Generalized linear model analysis revealed significant differences between the groups. The OCS+ group showed more severe prodromal symptoms ( = .007), worse functioning at baseline ( = .044) and during the previous year ( = .004), and more dysmorphophobic symptoms ( < .001) compared to the OCS- group. OCS+ patients were also more frequently treated with antidepressants ( = .004) than were OCS- patients. In our sample, among children and adolescents with CHR-P, the prevalence of OCS was high (50%). OCS+ subjects had a more severe clinical and functional profile than OCS- subjects. Early detection and treatment of these symptoms can lead to better outcomes for these patients.